KOMPOSISI JENIS DAN STRUKTUR VEGETASI HUTAN DATARAN RENDAH DI KOMPLEKS GUNUNG BULUSARAUNG SULAWESI SELATAN - Asrianny Asrianny; Catarina Balgis Paweka; Amran Achmad; Ngakan Putu Oka; Nida' Sari Achmad (PERENNIAL, 2019)
The Bulusaraung Mountain is a lowland forest and is one of the main ecosystems owned by Bantimurung Bulusaraung National Park. Therefore, this study aims to determine the species composition and vegetation structure of lowland forests in the complex of Bulusaraung Mountain. The research was conducted from April to May 2018. Data collection was carried out using a 20 × 20 meter plot placed on the Balleanging, Tokaddaro  and Tompobulu track lines based on altitude (550 m asl, 650 m asl, and 750 m asl). The result of this study show that there are 44  species were found on tree class, 65 species on  pole class,  40 species on  sapling class and  25 species on seedling class. The species composition in the study area was dominated Palaquium obovatum, Persea rimosa, Arthrophyllum diversifolium, Cryptocarya laevigata, and Engelhardia serrata, while Psychotria leptothyrsa, Antidesma bunius, Maesa ramentacea, Ficus sandpaper, Baccaurea javanica, Symplocos maliliency, Callicarpa pentandra, and Saurauia tristyla is a type of tree that differentiates at each altitude. The structure of the forest canopy layer at an altitude of 550 m above sea level consists of three canopy layers, while at an altitude of 650 and 750 m above sea level consisting only of two canopy layers. The cover of forest canopy in all sampling locations was reached 75-90%.